Silk for post-harvest horticultural produce safety and quality control. (January 2023) - Tracey, Chantal T.; Kryuchkova, Anastasia V.; Bhatt, Takshma K.; Krivoshapkin, Pavel V.; Krivoshapkina, Elena F.
Abstract: A third of food produced for human consumption is wasted on the way from the farm to the table. This is very evident in fruits and vegetables, perishable foods that are particularly susceptible to physical, chemical, and microbiological spoilage, resulting in poor appearance, smell, taste, and texture, as well as a shorter shelf life. This has prompted the exploration of different preservation techniques. One of the proposed methods is the use of biodegradable biocompatible silk-based food-friendly coatings with antimicrobial properties. Recently, several types of silk-based intelligent and active food packaging have also been proposed, proving that silk has many potential applications in the food industry. This review explores spider silk and silk fibroin as potential food coatings and smart packaging for prolonging fruit and vegetable freshness. Graphical abstract: Silk is a very versatile biomaterial that has piqued the interest of the food industry over the past two decades. This has led to the emergence of silk-based food coatings and smart packaging that ensure that consumers receive safe, high-quality food products. Image 1 Highlights: Horticultural produce preservation. Silk-based food coatings for food quality and safety control. Intelligent and active silk-based food packaging.